Skip to content

Commit

Permalink
done 3.8
Browse files Browse the repository at this point in the history
  • Loading branch information
marcbezem committed Jan 31, 2024
1 parent 04c44e4 commit a60168a
Showing 1 changed file with 38 additions and 25 deletions.
63 changes: 38 additions & 25 deletions circle.tex
Original file line number Diff line number Diff line change
Expand Up @@ -2908,14 +2908,17 @@ \section{The \texorpdfstring{$m$\th}{mᵗʰ} root:

A key ingredient for the converse is the following.
\begin{lemma}\label{lem:X-mod-m-chosen}
Let $(X,t):\Cyc$ be a cycle with a chosen point $x_0:X$
and with order divisible by $m$.
Let $(X,t):\Cyc$ be a cycle with order divisible by $m$
and let $x_0$ be an element of $X$.
Then the map $f : \bn m \to X/m$, $f(k) \defeq [t^k(x_0)]$
is an equivalence.
\end{lemma}
\begin{proof}
Fix an equivalence class $V:X/m$ and consider its preimage under $f$,
$f^{-1}(V) \jdeq \sum_{k:\bn m}(V=[t^k(x_0)])$.
Fix an equivalence class $V:X/m$\marginnote{%
Here we take $V$ not as a set, but as an element of the set $X\to\Prop$.
See the discussion after \cref{lem:subtype-eq-=} for the distinction.}
and consider its
preimage under $f$, $f^{-1}(V) \jdeq \sum_{k:\bn m}(V=[t^k(x_0)])$.
The contractibility of this type is a proposition, so we may choose
$x:X$ with $V=[x]$.
Then $(V=[t^k(x_0)])\equiv([x]=[t^k(x_0)])\equiv(x\sim_m t^k(x_0))$.
Expand All @@ -2926,40 +2929,49 @@ \section{The \texorpdfstring{$m$\th}{mᵗʰ} root:
Then $x = t^n(x_0) \sim_m t^r(x_0)$, so we have our center.
Let $k:\bn m$ also satisfy $x\sim_m t^k(x_0)$.
We need to show the proposition $k=r$.
But $t^{r-k}(x_0) \sim_m x_0$, so we may take $q:\zet$ with $t^{qm+r-k}(x_0)=x_0$.
But $t^{r-k}(x_0) \sim_m x_0$, so we may take $q':\zet$
with $t^{q'm+r-k}(x_0)=x_0$.
Since $m$ divides the order of $t$, this implies $r=k$, as desired.
\end{proof}
Now we have all the pieces needed to prove the main result.
\begin{theorem}\label{thm:fiber-cdg}
For \emph{any} cycle $(X,t)$, the preimage $\cdg{m}^{-1}(X,t)$
is equivalent to $P\times X/m$,
where $P\defeq (m \mid \ord(t)) \jdeq (H_t \subseteq m\zet)$
expresses that $m$ divides the order of $t$.
\end{theorem}
\begin{proof}
\begin{construction}\label{thm:fiber-cdg}
For \emph{any} cycle $(X,t)$, we have an equivalence
between $\cdg{m}^{-1}(X,t)$ and
$P\times X/m$, where $P$ expresses that $m$
divides the order of $t$, formally
$P \defeq (H_t \subseteq m\zet)$ (see \cref{def:Order}).\footnote{%
When $X$ is a decidable set then LPO allows for a simpler formulation:
Then $P$ is either false, in which case $\cdg{m}^{-1}(X,t)$ is empty,
or true, in which case the preimage is $X/m$.
}
\end{construction}
\begin{implementation}{thm:fiber-cdg}
We'll use \cref{lem:weq-iso}, and we first define the function
\[
g : \cdg{m}^{-1}(X,t) \to P\times X/m,
\]
by mapping $(Y,u)$ and an identification of cycles
$e : (X,t) = (\bn m\times Y,\sqrt[\uproot{2}m]{u})$
$e : (X,t) \eqto (\bn m\times Y,\sqrt[\uproot{2}m]{u})$
to the proof of $P$ from \cref{lem:m-root-id}
and the class $V_e\defeq [e^{-1}(0,y)]:X/m$, for any $y:Y$.
Note that this doesn't depend on $y$, so that \cref{thm:wconstant-elim} applies.
and the class $V_e\defeq [e^{-1}(0,y)]:X/m$, for any $y:Y$.\footnote{%
Note that this doesn't depend on $y$, so that \cref{thm:wconstant-elim}
applies: $(0,y)$ and $(0,y')$ are a distance $mr$ apart,
and $e^{-1}$ preserves this distance.}
As a subset of $X$, $V_e=\setof{x:X}{\fst(e(x))=0}$.

In the other direction, to define the function
\[
h : P\times X/m \to \cdg{m}^{-1}(X,t),
\]
fix an equivalence class $V:X/m$,
fix an equivalence class $V$ of $X/m$,
and assume that $m$ divides the order of $t$.
Then we have, with a bit of abuse of notation, the cycle $(V,t^m)$,
where we also write $V$ for the type of elements in $X$ that lie in the class $V$,
and $t^m$ is the restriction of this power of $t$ to $V$.\footnote{%
If $x$ lies in $V$, then so does $t^m(x)$.}
As in the discussion after \cref{xca:pointed-maps-circle},
we take $V$ as the set of elements in $X$ that lie in the class $V$.
Then $(V,t^m)$ is a cycle.\footnote{%
Indeed $t^m$ is properly restricted to $V$: If $x$ lies in $V$,
then so does $t^m(x)$.}
We also need an identification
$(X,t)=(\bn m\times V,\sqrt[\uproot{2}m]{t^m})$.
$(X,t)\eqto\cdg{m}(V,t^m)\jdeq(\bn m\times V,\sqrt[\uproot{2}m]{t^m})$.
This we define via a map $e : \bn m\times V \to X$, $e(k,x) \defeq t^k(x)$.
This is an equivalence as long as the orders match.
So let $n:\zet$, and assume first that $t^n=\id$.
Expand All @@ -2968,17 +2980,18 @@ \section{The \texorpdfstring{$m$\th}{mᵗʰ} root:
\[
(\sqrt[\uproot{2}m]{t^m})^n
= (\sqrt[\uproot{2}m]{t^m})^{qm}
= (\id \times t^m)^q = (\id \times t^{qm}) = \id.
= (\id \times t^m)^q = (\id \times t^{mq})
= (\id \times \id_V)= \id.
\]
Conversely, we know from \cref{lem:m-root-id} again,
that if $(\sqrt[\uproot{2}m]{t^m})^n=\id$,
then we may write $n=qm$ for some $q:\zet$,
and $(t^m)^q=\id$, which by \cref{lem:cycle-order-point-ap}
implies that $t^n = \id$.
and $(t^m)^q=\id_V$, which by \cref{lem:cycle-order-point-ap}
implies that $t^n = \id_X$.

Straight from these definitions, we see that $g\circ h=\id$.
We leave to the reader to check that $h\circ g=\id$.
\end{proof}
\end{implementation}

\section{Higher images}
\label{sec:higher-images}
Expand Down

0 comments on commit a60168a

Please sign in to comment.